9s^2+3s-20=x

Simple and best practice solution for 9s^2+3s-20=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9s^2+3s-20=x equation:


Simplifying
9s2 + 3s + -20 = x

Reorder the terms:
-20 + 3s + 9s2 = x

Solving
-20 + 3s + 9s2 = x

Solving for variable 's'.

Combine like terms: x + -1x = 0
-20 + 3s + 9s2 + -1x = 0

The solution to this equation could not be determined.

You can always share this solution

See similar equations:

| (x-1)(x^2-4)+2(x-1)(x+2)=(x-1)P | | 9x^2-4.5x-3.5=0 | | 6x^2-5x-14=0 | | x^4-7x-18=0 | | x^2-8x+18=0 | | x^2-8b+18=0 | | 30a^2+am-m^2=0 | | 30a^2+am-m^2=o | | 12s^2+11st-5t^2=0 | | 14x^2+11yx-15y^2=0 | | 3x^2+8=0 | | -2v^2-v+12=-3v^2+6v | | x^2+15x-64=0 | | 2x^2+8x-2=0 | | 12x^2-x-20=0 | | 5x^2+13x+6=0 | | x^3-12x^2+35x=0 | | x^3-13x^2+30x=0 | | 6x^2+17x-45=0 | | x^4-3x^2+1=0 | | 5x^2-5x-3= | | 3x^2-13x+14=0 | | 6x^2+x-c=(cx-1)(3x+2) | | X*x=x^2 | | 9c=c^2 | | 3x^2-12=0 | | 3x^2-8=0 | | x^2+6=6x^2-16 | | 16x^2-25=0 | | .66x^2-36=0 | | .66x^2-32=0 | | 2x^2+7x+3=0 |

Equations solver categories